FAKTOR-FAKTOR PENENTU YANG MEMPENGARUHI RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016 - Diah Ulsa Uktrilina, 14.05.52.0223; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the factors – factors that affect stock returns in manufacturing companies. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2014-2016 The sampling technique is purposive sampling. Based on purposive sampling a sample of 65 companies. Data analysis technique used is multiple linear regression analysis. The result showed that each variable has a different effect, ROA provide positive and significant influence on stock returns, DER provide positive and not significant influence on stock returns, PER provide negative and significant influence on stock returns, EPS provide negative and not significant influence on stock returns. Keywords: Return On Asset (ROA) , Debt to Equity Ratio (DER), Price Earning Ratio (PER), Earning Per Share (EPS) and Return Saham.